Butterfly Community Structure in Ulem-ulem Forest, Southern Area of Mount Rinjani National Park - Syakila, Baiq Nike; Ilhamdi, M. Liwa; Wirajagad, Gde Cahyadi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The southern area of Mount Rinjani National Park (TNGR), serves a dual purpose as a tourist destination and a conservation zone under the management of the TNGR Office. Data and information on wildlife diversity, particularly butterflies, in this location are crucial for supporting the development of ecotourism. This study aims to analyze the butterfly community structure in Ulem-Ulem Forest. The research was conducted in July 2025 using a survey method with a sweeping net technique along three observation transects: a water stream transect, a mid-forest transect, and a forest edge transect adjacent to residential areas. The collected data were analyzed using the Shannon-Wiener diversity index, Simpson dominance index, and Pielou evenness index. The results identified 550 individual butterflies, classified into 28 species, 23 genera, and 4 families (Papilionidae, Nymphalidae, Pieridae, and Lycaenidae). The species diversity index (H') value was 3.15, the dominance index (D) value was 0.051, and the evenness index (E) value was 0.94. These results indicate that the butterfly community in the southern area of Mount Rinjani National Park (TNGR), no dominant species, and high evenness.